Perlindungan terhadap Pekerja Migran Indonesia di Arab Saudi Menurut UU No. 18 Tahun 2017 tentang Pekerja Migran Indonesia - Moch. Fikri Azzam N. S.; M. Husni Syam (Bandung Conference Series: Law Studies, 2022)
Abstract. This study discusses "Protection of Indonesian Migrant Workers in Saudi Arabia according to Law no. 18 of 2017 concerning the Protection of Indonesian Migrant Workers” stated in Law no. 18 of 2017 concerning the Protection of Indonesian Migrant Workers. The purpose of this study is to find out how the form of regulation and implementation of the protection of Indonesian migrant workers in Law no. 18 of 2017. This type of research is normative legal research, by reviewing the laws and regulations regarding the protection of migrant workers. Sources of data used in this study are secondary data sources consisting of primary, secondary and tertiary legal materials. Various problems that often occur in Indonesian migrant workers, especially those working in the informal sector, such as; violence/torture, harassment, human trafficking, unpaid wages, etc. These cases often occur in legal and illegal Indonesian migrant workers before work, during work and after work. Abstrak. Penelitian Ini membahas tentang “Perlindungan Terhadap Pekerja Migran Indonesia di Arab Saudi Menurut UU No. 18 Tahun 2017 Tentang Perlindungan Pekerja Migran Indonesia.” Tujuan penelitian ini untuk mengetahui bagaimana bentuk pengaturan maupun implementasi perlindungan pekerja migran Indonesia dalam Undang-Undang No. 18 Tahun 2017. Jenis penelitian ini adalah penelitian hukum normatif, dengan cara mengkaji peraturan perundang-undangan tentang perlindungan pekerja migran. Sumber data yang digunakan dalam penelitian ini adalah sumber data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier. Berbagai masalah yang sering terjadi pada pekerja migran Indonesia khususnya yang bekerja di sektor informal, seperti; kekerasan/penyiksaan, pelecehan, perdagangan manusia, gaji tidak dibayar, dsb. Kasus tersebut sering terjadi pada pekerja migran Indonesia legal maupun ilegal pada masa sebelum bekerja, selama bekerja dan setelah bekerja.